BUILDING CHARACTERS OF PROSPECTIVE SCHOOL TEACHERS THROUGH THE CULTURE OF LITERATION TO IMPROVE PROFESSIONALISM IN TEACHING - Puspita, Ari Metalin Ika; Udin Syaefudin Saud; Damaianti, Vismaia S. (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2018)
Quality character building needs to be fostered from an early age. Every human being has the potential for good character before birth, but this potential must be continuously fostered through socialization and education from an early age. The Role of Teachers on Character Education, namely the Teacher as a Learning Designer. Here teachers in accordance with the program proposed by the Ministry of National Education are required to play an active role in planning Teaching and Learning Activities by paying attention to various components in the learning system. Character education is a very important key in shaping a child's personality. Apart from at home, character education also needs to be applied in schools and in the social environment. In essence, education has a purpose to help humans become intelligent and grow into good human beings. Formal education is a path of education through school. As an effort to improve the quality of character education, including: character education must contain moral values, character education must also involve aspects of moral knowing, moral feeling, and moral action, the implementation of the character education curriculum must be carried out, applying the concept of DAP (Developmentally Appropriate Practices), using an integrated learning system based on character, character education must be in accordance with the stages of children's moral development, in addition to the need for cooperation with parents of students (co-parenting).